Edukasi Pengelolaan Stres Sebagai Upaya menjaga Kesehatan Kulit - Rizqa Salsabila Firdausia; Endah Kurniawati; Mufrod (Universitas Jenderal Achmad Yani Yogyakarta, 2023)
ABSTRACT Stress is a problem that often arises in this modern era. Stress can be acute or chronic and is determined by individual perceptions and the body's response to the pressure. Long-term exposure to continuous stress can lead to physical illness in the body (psychosomatic), one of them is skin. Unhealthy skin will also cause a decrease in self-confidence, causing stress. Therefore there is a need for psychotherapeutic intervention to overcome these disorders and to restore the body's condition. Strategies that can be done to deal with stress can include an active approach to the source of stress, seeking social support (emotional support or information from other people or seeing a psychologist) from the surrounding environment, building self-control (self-control) towards the source of the problem, as well as trying to find a positive side from stress. So that this service activity is expected to be able to educate the public, especially teenagers to be able to manage stress properly. The activity was carried out using the webinar method with 37 youth participants. The activity was carried out in 3 stages, namely pretest, limitation of material - discussion and post test. In the pretest and posttest stages the participants were given the same 5 questions. Based on the results of the pretest and posttest, it was found that there was an increase in the correct answers from 79.459% to 85.405%. This indicates that there is an increase in knowledge from the participants related to managing stress on skin health after the intervention. Based on this, it can be interpreted that community service activities with the theme